Negotiation and optimality in an economic model of global climate change - Hans W. Gottinger (Fondazione Eni Enrico Mattei (FEEM), 2000)
We suggest a two-country, two-sector model as a basis for the control of global climate change in which the dynamic time path of the world economy is analysed under the provision that the outcomes of a negotiation game generate the global optimal solution.
Keywords: D0; D6; H4; Q3; 330; Precautionary Principle; self-protection; self-insurance; comparative statics; information structure; Klimawandel; Internationale Umweltpolitik; Klimaschutz; Verhandlungstheorie; Theorie